Determination Of Employee Motivation Through Human Resource Training And Development: A Literature Review From A Human Resource Management Perspective - Andi Nurfiana Haz (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Employee work motivation remains one of the most important determinants of organizational performance, employee engagement, and long-term organizational sustainability. Human Resource (HR) training and development have been widely recognized as strategic interventions for enhancing employee motivation; however, existing findings remain fragmented across different organizational contexts and theoretical perspectives. This study aims to systematically review the relationship between HR training and development and employee work motivation through the lens of Herzberg’s Two-Factor Theory. A literature review approach was employed by analyzing 16 peer-reviewed articles published between 2020 and 2025. Articles were identified through searches in Google Scholar, Scopus, ScienceDirect, Emerald Insight, SpringerLink, and Wiley Online Library using predefined keywords related to training, development, motivation, and Human Resource Management. The selected studies were screened based on relevance, publication quality, and alignment with the study objectives, and subsequently analyzed using thematic synthesis. The findings indicate that HR training and development positively influence employee motivation by strengthening Herzberg’s motivator factors, including achievement, recognition, responsibility, career advancement, and personal growth, while also improving hygiene factors such as supervision quality, working conditions, and organizational policy clarity. The review further identifies perceived organizational support, self-efficacy, organizational commitment, and management support as important mediating and moderating factors that influence the effectiveness of training initiatives. The novelty of this study lies in its integration of contemporary Human Resource Management literature with Herzberg’s Two-Factor Theory to provide a comprehensive explanation of how training and development shape employee motivation in modern organizations. The findings contribute to the advancement of HRM theory by offering an integrated conceptual understanding of the training–motivation relationship. Practically, the study suggests that HR managers should design continuous training, coaching, mentoring, and career development programs that not only enhance employee competencies but also foster sustainable motivation, engagement, and organizational commitment.